Relationship Among Serum Homocysteine, Serum Folate And Left Ventricular Ejection Fraction In Chronic Kidney Disease - Barua, Prasun; Haque, Mahmudul; Khan, Md Jahangir (Journal of Chittagong Medical College Teachers’ Association, 2018)
Background: Homocysteine (Hcy) a sulfurcontaining, non-protein a-amino is now considered an independent non-traditional risk factor for vascular disease. In Chronic Kidney Disease (CKD) highly prevalent hyperhomocysteinemia which is often associated with decreased folate concentrations is thought to contribute to increased cardiovascular morbidity. So, the aim of this cross-sectional study was to investigate the relations among serum homocysteine, serum folate and Left Ventricular Ejection Fraction (LVEF) in the context of native CKD patients. Materials and methods: A total of one-thirty (130) participants were recruited between June and July 2016. Among them ninety (90) were CKD patients of stage III, IV & V and forty (40) were healthy controls.eGFR was calculated by MDRD formula. Different groups were created based on serum homocysteine level and eGFR. Results: In this study, hyperhomocysteinemia was seen in 97% CKD patients compared to 52.50% in controls. The CKD patients with elevated homocysteine levels had higher serum creatinine, LDL and systolic BP but they had lower eGFR, serum folateand LVEF than those with normal homocysteine concentrations. As the severity of homocysteinemia increased, eGFR and serum folate decreased. LVEFalso reduced significantly with increasing severity of hyperhomocysteinemia i.e. from 68% in those withouthyperhomocysteinemia to 41.33% in those with severe hyperhomocysteinemia. Chi-squared tests and odds ratios proved significant associations of hyperhomocysteinemia and folate deficiency with CKD. Higher homocysteine concentrations were also associated with low folate and low LVEF. Here, serum homocysteine correlated negatively with eGFR, serum folate and LVEF and positively with LDL and systolic BP. Conclusion: Inconclusion, this study revealed significant associationsamong hyperhomocysteinemia, low serum folate and low LVEF in the native CKD patients. The consistency of homocysteine- eGFR and homocysteine-LVEF correlations suggests that serum homocysteine may provide useful additional information about CKD and associated high cardiovascular morbidity. JCMCTA 2018 ; 29 (1) : 35-41